KESIAPAN MENTAL PENYULUH AGAMA KRISTEN DALAM MENGHADAPI TANTANGAN MASYARAKAT DI MALILI KABUPATEN LUWU TIMUR - Memei Memei; Esti Arruan, Desti Natalia Pagassang, Indah Lestari, Kristiani Ningsi Pabontong (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Christian religious instructors have a very important role in community life, where instructors are tasked with helping solve problems faced by the community. As an instructor, mental readiness is a very important aspect in carrying out the role. Where when instructors interact with the community, instructors need to have very deep empathy to understand the problems faced by a person or group. Apart from that, extension workers must also have great patience in listening and providing support to the community. In situations that may be tense or stressful, the instructor's ability to remain calm and manage his/her spirit remains key. Extension workers who have good mental health are also able to maintain professionalism, not get carried away by emotions, and remain focused on providing the help the community needs. Not only in terms of mental readiness in society, but also what must be paid attention to is in worship. An instructor's mental readiness can influence the way they respond to problems that arise in everyday life. The mental readiness of a Christian religious instructor will be mentally ready and able to provide emotional support and advice to people in need.